METHODS OF TEACHING FOREIGN LANGUAGES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article provides an overview of the main methods of teaching foreign languages, including Grammar-Translation, Direct Method, Audio-Lingual Method, Communicative Language Teaching (CLT), Task-Based Language Teaching (TBLT), technology-enhanced learning, and Content and Language Integrated Learning (CLIL). The article discusses te features, advantages, and limitations of each approach, emphasizing the importance of adapting methods to specific educational contexts for effective language acquisition.